Pemeriksaan Proses Pengolahan Air Minum Isi Ulang terhadap Jumlah Bakteri dan Pengujian Bakteriologi di Depot Tiban Kota Batam - Deny Soryatmodjo (Universitas Pahlawan Tuanku Tambusai, 2021)
Water is something important in life. Humans, animals and plants cannot continue their life without water. This service aims to determine the quality of Refill Drinking Water Bacteriologically according to the Regulation of the Minister of Health of the Republic of Indonesia Number 492/MENKES/PER/IV/2010. The samples used two Depots A and B refilled drinking water, each water sample was taken in three processing sections, namely raw water, water after passing through the filter cartridge, and water after passing through Ultraviolet. The method used is Total Plate Number and Most Probable Number using 3 tubes. The results of the Bacteriological Examination of the Refill Drinking Water Examination showed a decrease in the number of bacteria in the Refill Drinking Water treatment, and the Most Probable Number (MPN) of Escherichia Coli. This indicates that the refill drinking water at the two depots was not found to have bacteriological contamination. One of the efforts to prevent microbiological pollution is to always carry out maintenance, use standard equipment, and select good raw water, in order to maintain product quality so that it does not endanger consumers or the surrounding community.